Endoscopic management of enteral tubes in adult patients – Part 2: Peri- and post-procedural management. European Society of Gastrointestinal Endoscopy (ESGE) Guideline - Gkolfakis, Paraskevas; Arvanitakis, Marianna; Despott, Edward J.; Ballarin, Asuncion; Beyna, Torsten; Boeykens, Kurt; Elbe, Peter; Gisbertz, Ingrid; Hoyois, Alice; Mosteanu, Ofelia; Sanders, David S.; Schmidt, Peter T.; Schneider, Stéphane M.; van Hooft, Jeanin E. (Endoscopy, 2020)
ESGE recommends the “pull” technique as the standard method for percutaneous endoscopic gastrostomy (PEG) placement.Strong recommendation, low quality evidence.ESGE recommends the direct percutaneous introducer (“push”) technique for PEG placement in cases where the “pull” method is contraindicated, for example in severe esophageal stenosis or in patients with head and neck cancer (HNC) or esophageal cancer.Strong recommendation, low quality evidence.ESGE recommends the intravenous administration of a prophylactic single dose of a beta-lactam antibiotic (or appropriate alternative antibiotic, in the case of allergy) to decrease the risk of post-procedural wound infection.Strong recommendation, moderate quality evidence.ESGE recommends that inadvertent insertion of a nasogastric tube (NGT) into the respiratory tract should be considered a serious but avoidable adverse event (AE).Strong recommendation, low quality evidence.ESGE recommends that each institution should have a dedicated protocol to confirm correct positioning of NGTs placed “blindly” at the patient’s bedside; this should include: radiography, pH testing of the aspirate, and end-tidal carbon dioxide monitoring, but not auscultation alone.Strong recommendation, low quality evidence.ESGE recommends confirmation of correct NGT placement by radiography in high-risk patients (intensive care unit [ICU] patients or those with altered consciousness or absent gag/cough reflex).Strong recommendation, low quality evidence.ESGE recommends that EN may be started within 3 – 4 hours after uncomplicated placement of a PEG or PEG-J.Strong recommendation, high quality evidence.ESGE recommends that daily tube mobilization (pushing inward) along with a loose position of the external PEG bumper (1 – 2 cm from the abdominal wall) could mitigate the risk of development of buried bumper syndrome.Strong recommendation, low quality evidence.